The Asymmetric Experience of Positive and Negative Economic Growth: Global Evidence Using Subjective Well-Being Data - Jan-Emmanuel De Neve; George W. Ward; Femke De Keulenaer; Bert van Landeghem; Georgios Kavetsos; Michael I. Norton (Institute for the Study of Labor (IZA), 2015)
Are individuals more sensitive to losses than gains in terms of economic growth? Using subjective well-being data, we observe an asymmetry in the way positive and negative economic growth are experienced. We find that measures of life satisfaction and affect are more than twice as sensitive to negative economic growth as compared to positive growth. We use Gallup World Poll data from over 150 countries, BRFSS data on 2.5 million US respondents, and Eurobarometer data that cover multiple business cycles over four decades. This research provides a new perspective on the welfare cost of business cycles and has implications for growth policy and our understanding of the long-run relationship between GDP and subjective well-being.
Keywords: D03; O11; D69; I39; 330; economic growth; business cycles; subjective well-being